BROWNIES KACANG MERAH DAN DAUN KELOR SEBAGAI MAKANAN SELINGAN TINGGI PROTEIN DAN ZAT BESI BAGI SISWA SEKOLAH DASAR: BROWNIES OF RED BEANS AND MORINGA LEAF AS A HIGH PROTEIN AND IRON SUBSTANCE FOR ELEMENTARY SCHOOL STUDENTS - Ghassani, R Wulandari; Sumarjo, Dwi Nur Ida Islamiati; Widartika, Widartika; Saleky, Yohannes Willihelm; Sulaeman, Agus; Rahmat, Mamat (Jurnal Inovasi Bahan Lokal dan Pemberdayaan Masyarakat, 2023)
Consumption of vegetables and nuts in the community, especially elementary school age children is still low. Intake of vegetables and nuts can be obtained from snacks such as brownies. Red bean flour and moringa leaf flour which are added as ingredients for brownies can be used as snacks high in protein and iron in an effort to increase the intake of vegetables and nuts in elementary school-aged children. The aim of the study was to determine the effect of red bean flour and Moringa leaf flour formulations on organoleptic properties, protein content, and iron content. This research is an experimental study with a comparison formulation of red bean flour and Moringa leaf flour F1 50%: 50%, F2 70%: 30%, and F3 30%: 70%. The organoleptic test was carried out by 30 moderately trained panelists, then the best results were tested for protein content by the micro-kjeldahl method and iron content by the ICP-OES method. Data analysis used the Kruskal Wallis test, followed by the Mann Whitney test. Brownies that have the highest level of preference is the F2 formulation with a ratio of red bean flour and Moringa leaf flour 70%: 30%, color aspect 70% likes, aroma 63% likes, taste 84% likes, texture 80% likes and overall 84% likes . One serving is 60 grams and can meet 10.1% and 24.1%, respectively, of the daily protein and iron adequacy of elementary school-aged children. The results of statistical tests found significant differences between each product formulation. Further research can be done by adding jam or dried fruit to improve the scentand adding toppings to increase the attractiveness of the product as well as targeting research